Identification of DT104 and U302 Phage Types among Salmonella enterica Serotype Typhimurium Isolates by PCR - Pritchett, Lori C. (American Society for Microbiology, 2000)
A DNA sequence was identified in isolates of Salmonella enterica serotype Typhimurium definitive type 104 (DT104). The PCR amplification of an internal segment of this sequence identified DT104 and the closely related U302 phage type among 146 isolates of S. enterica serotype Typhimurium tested, thus providing a tool for rapid identification of DT104 and related isolates.